2005
DOI: 10.1080/00365540510027165
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for domestic sporadic campylobacteriosis among young children in Sweden

Abstract: A case-control study was conducted in Sweden to study risk factors for domestically acquired Campylobacter jejuni/coli infections among children aged less than 6 y. A total of 126 cases, reported to the national surveillance system were recruited over 1 y. Controls, selected from the population register, were matched to the cases by age, gender, place of residence and time of infection of the case. Information was gathered by posted questionnaires. Two separate conditional regression models were developed incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 14 publications
3
51
2
1
Order By: Relevance
“…Other frequently reported risk factors are consumption of unpasteurized milk [14,15,20], eating in a restaurant [14,17,19,21], contact with pets, especially puppies [13,14,16,19,22,23], contact with farm animals [13,14,17,19,20,23,24] and foreign travel [13-16, 19, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Other frequently reported risk factors are consumption of unpasteurized milk [14,15,20], eating in a restaurant [14,17,19,21], contact with pets, especially puppies [13,14,16,19,22,23], contact with farm animals [13,14,17,19,20,23,24] and foreign travel [13-16, 19, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Fullerton et al (2007) found the risk to be even higher for infants exposed to a pet with diarrhea in the home (OR 7.6; 95% CI=2.1-28) (Fullerton, 2007). Carrique-Mas et al (2005) found having a dog in the household to be a significant contributor to risk of Campylobacter infection (adjusted OR 3.8; 95% CI=1.5-…”
Section: Petsmentioning
confidence: 99%
“…Commonly reported risk factors for Campylobacter outbreaks include exposure to undercooked poultry 5 , unpasteurized milk, 6;7 and contaminated water 8 . Eating in restaurants 9 , not observing proper food preparation practices 10 and traveling abroad 9;11 , have also been associated with both outbreaks and sporadic (non-outbreak) cases of campylobacteriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Case-control studies of potential risk factors for campylobacteriosis have been undertaken in several countries [4][5][6][7][8][9][10][11] including Australia [12,13]. Consumption of chicken is the most commonly identified risk factor for sporadic campylobacteriosis.…”
Section: Introductionmentioning
confidence: 99%